2009
DOI: 10.1017/s1751731109004248
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime productivity of dairy cows in smallholder farming systems of the Central highlands of Kenya

Abstract: Evaluation of lifetime productivity is sensible to target interventions for improving productivity of smallholder dairy systems in the highlands of East Africa, because cows are normally not disposed of based on productive reasons. Feeding strategies and involuntary culling may have long-term effects on productive (and therefore economic) performance of dairy systems. Because of the temporal scale needed to evaluate lifetime productivity, experimentation with feedstuffs in single lactations is not enough to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 27 publications
(28 reference statements)
1
50
1
2
Order By: Relevance
“…D'autres perspectives de couplage sont Ă  envisager avec des modèles de nutrition et de production animale comme LIVSIM (Rufino et al, 2009), pour Ă©valuer la productivitĂ© des troupeaux pastoraux.…”
Section: Resultsunclassified
“…D'autres perspectives de couplage sont Ă  envisager avec des modèles de nutrition et de production animale comme LIVSIM (Rufino et al, 2009), pour Ă©valuer la productivitĂ© des troupeaux pastoraux.…”
Section: Resultsunclassified
“…However, in the lowinput low-output smallholder dairy production systems of the tropics, the lifespan of dairy cows is often decided not only by cow's milk yield, but also by the owner. For instances, Rufino et al (2009) reported that evaluation of lifetime productivity is important to target interventions for improving productivity of smallholder dairy systems in the highlands of East Africa, because cows are normally not disposed off based on productive reasons, rather it is determined by feeding strategies and involuntary culling. In such systems, voluntary culling of dairy cows is rarely practiced because farmers that have few animals face difficulties to spread risk.…”
Section: Introductionmentioning
confidence: 99%
“…Parturition could increase while mortality rate could fall due to better pasture intake. Rufino et al (2009) find that adding supplements to diets increases calving rate among smallholder Kenyan dairy farms. Huttner et al (2001) reports that malnutrition is a major factor predisposing cattle to poor health among Malawian smallholders.…”
Section: Impact Of Land Degradation or Improvement On Livestock Produmentioning
confidence: 88%